2021
DOI: 10.1055/s-0041-1731045
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' Heightened Stress Responses to Recounting their NICU Experiences Months after Discharge: A Mixed Methods Pilot Study

Abstract: Objective The acute and traumatic events associated with having a newborn who requires admission to the neonatal intensive care unit (NICU) may elicit long-term concerns for parents postdischarge. Cognitive processing of taxing events influences recurring stress responses, which can be inferred via biomarkers such as salivary cortisol (sCort) and skin conductance (SC). In addition, personal narratives provide an important insight into individual perceptions and coping strategies. The current pilot study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Prior research has demonstrated greater stress related to role alterations for mothers compared with fathers 18 28. Still other research has highlighted unique stressors for fathers in the NICU including divided attention between infant and partners 29 30. In this study, we found that mothers reported less parental stress than fathers.…”
Section: Discussionmentioning
confidence: 44%
“…Prior research has demonstrated greater stress related to role alterations for mothers compared with fathers 18 28. Still other research has highlighted unique stressors for fathers in the NICU including divided attention between infant and partners 29 30. In this study, we found that mothers reported less parental stress than fathers.…”
Section: Discussionmentioning
confidence: 44%
“…Parental feelings of stress and depression may be new in onset or be exacerbated by preexisting individual and extrinsic risk factors. Salivary stress biomarkers, e.g., salivary cortisol, coupled with validated screening questionnaires, an approach not previously much used 51 , are useful tools in detecting parents at risk for stress and depression following their infants' NICU admission. Of note, we did not find a close association between infant illness severity or signs of ICU management, measured by the NTISS, with parental PPD or stress/anxiety.…”
Section: Discussionmentioning
confidence: 99%